Pemberdayaan Remaja melalui Pelatihan Konselor Sebaya pada Komunitas Yayasan Setara Kota Semarang (Indonesian Version) - Ratna Cempaka Louk Fanggi; Fitri Anysa; Erlangga Ananda; Nur Fayuna A.; Sigit Hariyadi; Ashari Mahfud; Awalya Awalya (Sejahtera: Jurnal Inspirasi Mengabdi Untuk Negeri, 2026)
Youth under the guidance of Yayasan Setara Semarang are categorized as vulnerable groups facing risks of school dropout and violence, often repressing emotional distress due to high mental health stigma and lack of structured counseling access. This community service program aimed to enhance the capacity for empathetic communication, basic counseling skills, and basic Psychological First Aid (PFA) among peer youths. The program implemented experiential and observational learning approaches through a structured training method including interactive lectures, clinical modeling, and guided roleplays. The participants consisted of 19 youth representatives from the assisted areas of Yayasan Setara. The training was successfully conducted and stimulated social transformation within the community. Qualitatively, the program initiated interpersonal behavioral shifts from listening to reply to listening to understand, boosted the participants’ social self-efficacy as local leaders (agents of change), and established a new informal social institution called "Pos Curhat Sebaya" (Peer Counseling Corner) as a frontline community support system. This intervention effectively optimized the youths’ existing roles as active pioneers and reporters (2P) for child rights, making them self-reliant subjects in maintaining community well-being.